2021
DOI: 10.1039/d1ma00733e
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of biodegradable implants: emerging trends in bioactive ceramic coatings and mechanical treatments

Abstract: Surface of an implant plays a key role in determining the performance as several events are associated with the surface. Modifying the surface with a bioactive coating or/and mechanical treatment can profoundly affect the success of the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 222 publications
(197 reference statements)
0
20
0
Order By: Relevance
“…These techniques including shot peening, ultrasound shot peening (USSP), laser shock peening (LSP), surface mechanical attrition treatment (SMAT), and ball burnishing, etc. are primarily designed to improve the tribological properties of the metallic part by inducing near-surface compressive residual stress [ 27 , 28 , 29 , 30 , 31 ]. However, the investigation of the corrosion resistance influenced by these strategies has also shown that these techniques can be exploited for the simultaneous improvement in the fatigue and degradation life of magnesium structures [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Surface Cleaning and Pre-treatmentmentioning
confidence: 99%
“…These techniques including shot peening, ultrasound shot peening (USSP), laser shock peening (LSP), surface mechanical attrition treatment (SMAT), and ball burnishing, etc. are primarily designed to improve the tribological properties of the metallic part by inducing near-surface compressive residual stress [ 27 , 28 , 29 , 30 , 31 ]. However, the investigation of the corrosion resistance influenced by these strategies has also shown that these techniques can be exploited for the simultaneous improvement in the fatigue and degradation life of magnesium structures [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Surface Cleaning and Pre-treatmentmentioning
confidence: 99%
“…15,16 Other ceramics, such as vanadium oxide, are reported to be toxic at high concentrations, 17 whereas europium oxide has been investigated as a proangiogenic agent mediated by increased ROS production. 18 In comparison, ceria has been known to have low cell toxicity along with ROS scavenging, osteogenic activity, and antibacterial potential.…”
Section: Introductionmentioning
confidence: 99%
“…Surface functionalization is a viable strategy to impart bioactivity to PLA scaffolds. 18,25 The goal of this work was to investigate the potential of redox-modulating ceria nanoparticles to promote stem cell osteogenesis and inhibit bacterial growth on 3D-printed scaffolds for bone tissue engineering. We prepared porous PLA scaffolds by FFF and established a strategy for surface functionalization with ceria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations